Seroprevalence and levels of anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies among medical students: possible associated factors in Northeastern Brazil - Mara Silva Coelho, Tania; Ana Luiza Rabelo Saldanha, Ana; Rita Máximo Julião, Maria; Fontelles Brasil, Lívia; Montenegro de Carvalho Araújo, Fernanda; Helena Gambim Fonseca, Marcela; Francilene Souza Silva , Maria; Dinelly Pinto, Ana Carolina; Rodrigues Carvalho, Maria Raquel; Henrique Alencar, Carlos; et al. (Journal of Health & Biological Sciences, 2024)
Objective: we evaluated the seroprevalence and levels of anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies among medical students and the possible associated factors. Methods: a survey was conducted using the data collected in November 2020 and February 2022 in Fortaleza, Northeast Brazil. A questionnaire was administered, and blood and nasopharyngeal swab samples were collected. The Abbott test was used for the assessment of humoral response to the SARS-CoV-2 spike (S) and nucleocapsid (N) proteins. The total antibodies were detected using a SARS-CoV-2 antibody test (Wodfo). Swab samples were subjected to qualitative detection of viral RNA. Chi-square test and multinomial logistic regression analysis were performed using SPSS and GraphPad Prism. Results: the seroprevalence rate in 2020 was 6.22% (40/643), and no difference in prevalence was observed between the semesters (p=0.520). The seroconversion rate was 51.1%. The seropositivity rates were 48.9% for N antibodies and 100% for S antibodies. The antibody response to N protein was higher in 2022 (p<0.001). Loss of smell was the most prevalent positive symptom (p=0.032). The adherence rate to protection measures was >75%. Most students reported a decrease in family income (63.7%), an increase in anxiety (82.6%), and a negative impact on their mental health (85.7%) regardless of the seroconversion status. The worst indicators of mental health quality were observed in students who attended classes up to the eighth semester (p<0.001). Conclusion: students showed lower immune response than the general population, with excellent adherence to the preventive and control measures. Medical schools played an important role in the formation but not transmission.